A laws of war review of contemporary land-based missile defence system ‘Iron Dome’ - Block, Joel (Scientia Militaria - South African Journal of Military Studies, 2017)
Automated precise guided missile defence has been around for some years, and is a modern-day mechanism used frequently since 2011 to defend against rocket attacks penetrating national airspace. Israel’s automated Iron Dome Missile Defence System has intercepted over 1 000 rockets during two recent military campaigns, namely Operation Pillar of Defence in 2012 and Operation Protective Edge in 2014. This ‘human-in-the-loop’ technology may become increasingly normal in urbanised cities as states look to strengthen their aerial defence capabilities. However, the deployment of advanced sensor-based technology on the battlefield was predicted by the International Committee of the Red Cross (ICRC) in its 1987 Commentary to Additional Protocol I to bring about potentially disastrous consequences. Numerous roboticists, lawyers, and scientists have expressed concern, calling for a ban on similar fully autonomous weapon systems. There is no definitive answer yet as to the legality of actively deploying such a weapon system against rocket attacks. This article considers individual technological design choices made by Iron Dome’s manufacturer Rafael Advanced Defence Systems (Rafael) and explains trends as military efficiency is enhanced and legal provisions appear to be honoured within separate elements of the weapon system. Assessing the legalities and efficiencies of Iron Dome could inform future missile defence systems like Denel’s Cheetah Skyshield.